Reductions in Methicillin-resistant Staphylococcus aureus, Clostridium difficile Infection and Intensive Care Unit–Acquired Bloodstream Infection Across the United Kingdom Following Implementation of a National Infection Control Campaign - Edgeworth, Jonathan D (Clin Infect Dis, 2020)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) and Clostridium difficile infections declined across the UK National Health Service in the decade that followed implementation of an infection control campaign. The national impact on intensive care unit (ICU)-acquired infections has not been documented. METHODS: Data on MRSA, C. difficile, vancomycin-resistant Enterococcus (VRE), and ICU–acquired bloodstream infections (UABSIs) for 1 189 142 patients from 2007 to 2016 were analyzed. Initial coverage was 139 ICUs increasing to 276 ICUs, representing 100% of general adult UK ICUs. RESULTS: ICU MRSA and C. difficile acquisitions per 1000 patients decreased between 2007 and 2016 (MRSA acquisitions, 25.4 to 4.1; and C. difficile acquisitions, 11.1 to 3.5), whereas VRE acquisitions increased from 1.5 to 5.9. There were 13 114 UABSIs in 1.8% of patients who stayed longer than 48 hours on ICU. UABSIs fell from 7.3 (95% confidence interval [CI], 6.9–7.6) to 1.6 (95% CI, 1.5–1.7)/1000 bed days. Adjusting for patient factors, the incidence rate ratio was 0.21 (95% CI, 0.19–0.23, P < .001) from 2007 to 2016. The greatest reduction, comparing rates in 2007/08 and 2015/16, was for MRSA (97%), followed by P. aeruginosa (81%), S. aureus (79%) and Candida spp (72%), with lower reductions for the coliforms (E. coli 57% and Klebsiella 49%). CONCLUSIONS: Large decreases in ICU-acquired infections occurred across the UK ICU network linked with the first few years of a national infection control campaign, but rates have since been static. Further reductions will likely require a new intervention framework.